2017
DOI: 10.1111/1462-2920.13710
|View full text |Cite
|
Sign up to set email alerts
|

MST50 is involved in multiple MAP kinase signaling pathways in Magnaporthe oryzae

Abstract: Appressorium formation plays a critical role in Magnaporthe oryzae. Mst50 is an adapter protein of the Mst11-Mst7-Pmk1 cascade that is essential for appressorium formation. To further characterize its functions, affinity purification was used to identify Mst50-interacting proteins (MIPs) in this study. Two of the MIPs are Mst11 and Mst7 that are known to interact with Mst50 for Pmk1 activation. Surprisingly, two other MIPs are Mck1 and Mkk2 that are the upstream kinases of the Mps1 pathway. Domain deletion ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 79 publications
(161 reference statements)
0
75
0
Order By: Relevance
“…Recent interaction analysis of Mst50 protein revealed that the sterile alpha domain exclusively interacts with an upstream protein kinase Mck1 associated with the MPS1 pathway under cell wall and cell membrane-directed oxidative stress (Li et al 2017a). More so, the Mst50-Histidine kinase (Hik1) interaction promotes the phosphorylation of Osm1 under similar oxidative stress conditions (Li et al 2017a). This confirms the existence of pathway crosstalk among the components of MAPK signalling cascade during fungal development and stress response.…”
Section: Signal Transducing Cascades Associated With Appressorium Formentioning
confidence: 99%
“…Recent interaction analysis of Mst50 protein revealed that the sterile alpha domain exclusively interacts with an upstream protein kinase Mck1 associated with the MPS1 pathway under cell wall and cell membrane-directed oxidative stress (Li et al 2017a). More so, the Mst50-Histidine kinase (Hik1) interaction promotes the phosphorylation of Osm1 under similar oxidative stress conditions (Li et al 2017a). This confirms the existence of pathway crosstalk among the components of MAPK signalling cascade during fungal development and stress response.…”
Section: Signal Transducing Cascades Associated With Appressorium Formentioning
confidence: 99%
“…Ras-association domain was not important for response to oxidative stress (Li et al 2017). M.oryzae Ras2 is therefore essential for cellular viability, and a key mediator between both the Pmk1 MAPK and cAMP signalling cascades (Qi et al 2015;Zhou et al 2014).…”
Section: Recent Advances In Genome Sequencing the Availability Of Numentioning
confidence: 89%
“…Affinity purification was used to identify a series of Mst50-interacting proteins (MIPs) as well as upstream kinases of the Mps1 pathway, and also the histidine kinase Hik1 (Li et al 2017). These interactions suggest a role for Mst50 in three different signalling pathways.…”
Section: Recent Advances In Genome Sequencing the Availability Of Numentioning
confidence: 99%
“…The M. oryzae strains Guy11, 70-15, Ku80 (Villalba et al, 2008), KV103 (Khang et al, 2010) and HopAI and HopI1 transformants generated in this study (Table 1) were routinely cultured on OTA plates or CM agar plates at 258C as described (Xu and Hamer, 1996;Zhao et al, 2005;Park et al, 2006). For assaying sensitivity to hyperosmotic stress, colony growth was assayed on CM plates with 1 M sorbitol (Dixon et al, 1999;Li et al, 2017). Vegetative hyphae harvested from 2-day-old liquid CM cultures were used for the preparation of protoplasts and isolation of genomic DNA, RNA and proteins as described (Nishimura et al, 2003;Zhao et al, 2005;Park et al, 2006).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%